1. ## moment-generating function

$Y$ have pdf $P(Y=k)=(k+1)p^2 q^k$, with $0and $q=1-p$ and $k=0,1,2,...$
Is easy prove that $M_{Y}(t)=p^2 (1-qe^t)^2$. Let $X=Y_1+\cdots Y_{24}$, with $Y_{i}$ with same distribution of $Y$
Calculate $M_{X}(t)$

Note: $M_Y (t)=E(e^{tk})$

2. Originally Posted by jorgeston
$Y$ have pdf $P(Y=k)=(k+1)p^2 p^k$, with $0and $q=1-p$ and $k=0,1,2,...$
Is easy prove that $M_{Y}(t)=p^2 (1-qe^t)^2$. Let $X=Y_1+\cdots Y_{24}$, with $Y_{i}$ with same distribution of $Y$
Calculate $M_{X}(t)$

Note: $M_Y (t)=E(e^{tk})$
I have no time now. I'll reply later if no-one else does.

3. $X = 24Y$. Note that $M_{aY+b} = e^{bt} M_{Y}(at)$. In this case, $b = 0$ and $a = 24$. So $M_{24Y}(t) = M_{X}(t) = p^2(1-qe^{24t})^{2}$.

4. Originally Posted by tukeywilliams
$X = 24Y$. Note that $M_{aY+b} = e^{bt} M_{Y}(at)$. In this case, $b = 0$ and $a = 24$. So $M_{24Y}(t) = M_{X}(t) = p^2(1-qe^{24t})^{2}$.
If you have reason, i don't understand why $Y_1=Y_2=\cdots = Y_{24}$

If this is true, implies $X=24Y$, but i am confused

5. Originally Posted by jorgeston
If you have reason, i don't understand why $Y_1=Y_2=\cdots = Y_{24}$

If this is true, implies $X=24Y$, but i am confused
*Ahem* Didn't you say in your question:

"with with same distribution of " ....?